Overcoming the Semantic Barrier and Developing the Ability to Use Communicative Tools. Part II. Psychotechnique - E.N. Soldatenkova (Культурно-историческая психология)
This article describes the psychotechnique of mediating (real-life, communicative) action in working with difficult children. We outline the stages and corresponding environments leading to turning points in the formation of consciousness[1] (mental model) of a child with ASD. It’s defined by restructuring interfunctional relations in the process of mediation and developing conceptual reflective interfunctional thinking (not only reflective functional thinking). The psychotechnique can be used in practice, both in work with difficult children and in general education in order to prevent the motivational disorders and to raise the age boundary by restructuring the performance of yet unformed function).